KETAHANAN PANGAN KELUARGA PESERTA PROGRAM PEMBERDAYAAN MASYARAKAT DI PEDESAAN - Tin Herawati; Basita Ginting; Pang S. Asngari; Djoko Susanto; Herien Puspitawati (Food and Nutrition Society of Indonesia, 2011)
The research objectives were to analyzed the family food security and its factors of the participants in the community empowerment program at rural area. The research design was crossectional study and the data collection technique used a survey method toward 300 families, and their specification were 140 families from the National Program of Community Empowerment (PNPM), 107 families from The Keluarga Harapan Program (PKH), 31 families from the Raksa Desa Program and 22 families from The Business Development Program of Rural Agribusiness (PUAP). The highest percentage (52.0%) of the family categorized into food vulnerable and as many as 37.3 percent was insecure category. It was found 10.7 percent families categorized into secure category. Base on the program, more than a half families of PKH group (50.5%) and PUAP (63.6%) are insecure category. Food vulnerable category is in PNPM group (60.0%) and Raksa Desa group (61.3%). The highest percentage (15.0%) thar categorized into secure category is in PNPM group. The factors which influence significantly toward the family food security are the income per capita, the family size and the asset.